Structural and Proteomic Changes in Viable but Non-culturable Vibrio cholerae - Brenzinger, Susanne; van der Aart, Lizah T.; van Wezel, Gilles P.; Lacroix, Jean-Marie; Glatter, Timo; Briegel, Ariane (Frontiers in Microbiology, 2019)
Aquatic environments are reservoirs of the human pathogen Vibrio cholerae O1, which causes the acute diarrheal disease cholera. Upon low temperature or limited nutrient availability, the cells enter a viable but non-culturable (VBNC) state. Characteristic of this state are an altered morphology, low metabolic activity, and lack of growth under standard laboratory conditions. Here, for the first time, the cellular ultrastructure of V. cholerae VBNC cells raised in natural waters was investigated using electron cryo-tomography. This was complemented by a comparison of the proteomes and the peptidoglycan composition of V. cholerae from LB overnight cultures and VBNC cells. The extensive remodeling of the VBNC cells was most obvious in the passive dehiscence of the cell envelope, resulting in improper embedment of flagella and pili. Only minor changes of the peptidoglycan and osmoregulated periplasmic glucans were observed. Active changes in VBNC cells included the production of cluster I chemosensory arrays and change of abundance of cluster II array proteins. Components involved in iron acquisition and storage, peptide import and arginine biosynthesis were overrepresented in VBNC cells, while enzymes of the central carbon metabolism were found at lower levels. Finally, several pathogenicity factors of V. cholerae were less abundant in the VBNC state, potentially limiting their infectious potential. This study gives unprecedented insight into the physiology of VBNC cells and the drastically altered presence of their metabolic and structural proteins.